Expansion of cancer germline antigen–specific cytotoxic T lymphocytes for immunotherapy - Deepa Kolaseri Krishnadas; Yali Wang; Kumaran Sundaram; Fanqi Bai; Kenneth G Lucas (Tumor Biology)
The cancer germline antigens MAGE-A1, MAGE-A3, and NY-ESO-1 can be used to target relapsed or therapy-resistant malignant solid tumors, and previous studies have demonstrated that these antigens can be epigenetically upregulated on the surface of tumor cells following exposure to low-dose demethylating chemotherapy agents, such as decitabine. The extent to which cancer germline antigen cytotoxic T lymphocytes can be reliably expanded from healthy donors has not been well characterized, specifically in terms of whether these T cells consistently kill antigen-bearing targets or simply produce interferon-γ in the presence of the antigen. Cancer germline antigen cytotoxic T lymphocytes were generated using conventional method and high-density lymphocyte culture method. We demonstrate that there is no difference in the extent of antigen-specific killing with or without CD25 depletion when interleukin-21 is added to the cultures. Cancer germline antigen–specific killer cells could be expanded from 8/12 healthy donors using overlapping peptide mixes derived from MAGE-A1, MAGE-A3, and NY-ESO-1 and from 7/9 healthy donors using HLA-restricted epitopes. Furthermore, cytotoxic T lymphocyte derived from 4/5 patients displayed specific cytotoxicity of target cells expressing respective cancer germline antigen and HLA partially matched tumor lines. High-density lymphocyte culture prior to stimulation with cancer germline antigen peptides resulted in antigen-specific cytotoxic T lymphocyte from healthy donors and patients from whom cancer germline antigen cytotoxic T lymphocyte culture with conventional methods was not feasible. These data demonstrate that MAGE-A1-, MAGE-A3-, and NY-ESO-1-specific T cells with antigen-specific cytotoxicity can be cultured from healthy donors and patient-derived cells making adoptive immunotherapy with these cytotoxic T lymphocyte feasible.